Exhaled Breath Markers for Nonimaging and Noninvasive Measures for Detection of Multiple Sclerosis - Broza, Yoav Y.; Har-Shai, Lior; Jeries, Raneen; Cancilla, John C.; Glass-Marmor, Lea; Lejbkowicz, Izabella; Torrecilla, Jose S.; Yao, Xuelin; Feng, Xinliang; Narita, Akimitsu; Muellen, Klaus; Miller, Ariel; et al. (ACS Chemical Neuroscience, 2017)
Multiple sclerosis (MS) is the most common chronic neurological disease affecting young adults. MS diagnosis is based on clinical characteristics and confirmed by examination of the cerebrospinal fluids (CSF) or by magnetic resonance imaging (MRI) of the brain or spinal cord or both. However, neither of the current diagnostic procedures are adequate as a routine tool to determine disease state. Thus, diagnostic biomarkers are needed. In the current study, a novel approach that could meet these expectations is presented. The approach is based on noninvasive analysis of volatile organic compounds (VOCs) in breath. Exhaled breath was collected from 204 participants, 146 MS and 58 healthy control individuals. Analysis was performed by gas-chromatography mass-spectrometry (GC-MS) and nanomaterial-based sensor array. Predictive models were derived from the sensors, using artificial neural networks (ANNs). GC-MS analysis revealed significant differences in VOC abundance between MS patients and controls. Sensor data analysis on training sets was able to discriminate in binary comparisons between MS patients and controls with accuracies up to 90%. Blinded sets showed 95% positive predictive value (PPV) between MS-remission and control, 100% sensitivity with 100% negative predictive value (NPV) between MS not-treated (NT) and control, and 86% NPV between relapse and control. Possible links between VOC biomarkers and the MS pathogenesis were established. Preliminary results suggest the applicability of a new nanotechnology-based method for MS diagnostics.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Biomarkers; breath; diagnosis; multiple sclerosis; sensors; spectrometry; volatile organic compound